Gambaran Kualitas Tidur Pada Pasien Gagal Jantung di Ruang ICCU RSUD dr. M. Yunus BengkuluTahun 2018 - Putri Mayang Sari; Yusran Hasymi; Marti Yuseva (Universitas Bengkulu, 2019)
Sleep quality is a condition where individuals are able to maintain sleep and receive REM and NREM sleep needs. In patients with heart failure pulmonary edema can reduce lung elasticity and improve respiratory work so that patients with heart failure experience dyspnoe, Orthopnoe / NPD (Dipsnoe Noctural Paroximal) which will feel good in a sitting position, and cough. This can lead to sleep disorders with difficulty entering the stage of sleep and difficulty maintaining sleep. Inadequate sleep and poor quality sleep can result in a balance of physiological and psychological disorders. Lack of sleep for long periods can cause other illnesses or worsen existing diseases. This study uses descriptive design, aiming to identify the sleep quality of heart failure patients in RSUD dr. M. Yunus Bengkulu. Sampling in this study used Purposive Sampling techniques according to the research criteria. This research was conducted on May 1 - May 5, 2018. The results of the study showed the majority of 5 people (50%) respondents had total sleep hours <5 hours. 6 people (60%) respondents need ? 30 minutes to start sleeping, 8 people (80%) respondents wake up 2-3 times a night, and 8 people (80%) respondents feel ranging from moderate to very sleepy when doing activities in the middle day. Based on the sleep quality of the respondents, the majority of respondents 6 people (60%) had poor sleep quality and only 4 people (40%) had good sleep quality.